Intimal Hyperplasia, Stenosis, and Arteriovenous Fistula Maturation Failure in the Hemodialysis Fistula Maturation Study - Cheung, Alfred K; Imrey, Peter B; Alpers, Charles E; Robbin, Michelle L; Radeva, Milena; Larive, Brett; Shiu, Yan-Ting; Allon, Michael; Dember, Laura M; Greene, Tom; Himmelfarb, Jonathan; Roy-Chaudhury, Prabir; et al. (Journal of the American Society of Nephrology, 2017)
Intimal hyperplasia and stenosis are often cited as causes of arteriovenous fistula maturation failure, but definitive evidence is lacking. We examined the associations among preexisting venous intimal hyperplasia, fistula venous stenosis after creation, and clinical maturation failure. The Hemodialysis Fistula Maturation Study prospectively observed 602 men and women through arteriovenous fistula creation surgery and their postoperative course. A segment of the vein used to create the fistula was collected intraoperatively for histomorphometric examination. On ultrasounds performed 1 day and 2 and 6 weeks after fistula creation, we assessed fistula venous stenosis using pre-specified criteria on the basis of ratios of luminal diameters and peak blood flow velocities at certain locations along the vessel. We determined fistula clinical maturation using criteria for usability during dialysis. Preexisting venous intimal hyperplasia, expressed per 10% increase in a hyperplasia index (range of 0%-100%), modestly associated with lower fistula blood flow rate (relative change, -2.5%; 95% confidence interval [95% CI], -4.6% to -0.4%; =0.02) at 6 weeks but did not significantly associate with stenosis (odds ratio [OR], 1.07; 95% CI, 1.00 to 1.16; =0.07) at 6 weeks or failure to mature clinically without procedural assistance (OR, 1.07; 95% CI, 0.99 to 1.15; =0.07). Fistula venous stenosis at 6 weeks associated with maturation failure (OR, 1.98; 95% CI, 1.25 to 3.12; =0.004) after controlling for case mix factors, dialysis status, and fistula location. These findings suggest that postoperative fistula venous stenosis associates with fistula maturation failure. Preoperative venous hyperplasia may associate with maturation failure but if so, only modestly.